Aboveground biomass and chemical composition of Urochloa grasses at different growth ages in the humid tropics - Ventura-Ríos, Joel; Maldonado-Peralta, María de los Ángeles; Santiago-Ortega , Mario Alberto; García-Salas , Alejandro; Rojas-García, Adelaido Rafael (Ecosistemas y Recursos Agropecuarios, 2025)
Urochloa grasses produce high biomass yields and their nutritional value is acceptable for ruminant feeding. The objective of this research was to evaluate the biomass of three Urochloa grasses (Cayman, Humidicola and Toledo) and to determine the best forage source based on their chemical composition and biomass yield under a warm subhumid climate. The work was carried out in 2020 in Isla, Veracruz, Mex. Annual biomass production and chemical composition were evaluated at four regrowth ages [RA; 30, 60, 90, and 120 d after regrowth (DAR)]. A completely randomized block experimental design with a split-plot arrangement was used, where: the large plot was the genotype and the small plot was the regrowth age (30, 60, 90, and 120) with three repetitions. The data were analyzed by analysis of variance (ANOVA) using the GLM/SAS procedure and the treatment means were compared with the Tukey test (ɑ=0.05). The biomass, hemicelluloses, lignin, and ash content was higher (p ≤ 0.05) at 120 DDR, being 19.5 t ha-1 year-1; 21.2, 7.0 and 12.2%, for Humidicola grass, respectively, while cellulose was higher in Toledo grass 41.1 %. Crude protein and acid detergent fiber (p ≤ 0.05) were higher than 30 DDR, 10% and 42.4% for Cayman and Humidicola, respectively. Humidicola, at 90 DDR, presented the highest value of neutral detergent fiber (66.2%, p ≤ 0.05), while the ether extract was not different between cultivars (p ≥ 0.05). According to biomass yield and chemical composition, Humidicola grass is a high-quality forage for ruminants in tropical conditions.